Pubertal Body Mass Index Change Is Associated With Adult Coronary Atherosclerosis and Acute Coronary Events in Men - Kindblom, Jenny M. (Arterioscler Thromb Vasc Biol, 2021)
OBJECTIVE: The aim with the present study was to evaluate the association between pubertal body mass index (BMI) change and adult coronary artery calcification (CAC) score and risk of acute coronary events. APPROACH AND RESULTS: We included 37 672 men from the BMI Epidemiology Study and calculated their pubertal BMI change (BMI at 20 years−BMI at 8 years). Coronary artery computed tomography analysis of CAC score, midlife BMI, and major risk factors for coronary heart disease were available for a sub-cohort through linkage with the SCAPIS (Swedish Cardio Pulmonary Bioimage Study) cohort (n=922). Information on first acute coronary events was retrieved from Swedish national registers (n=37 672, events n=1873). Pubertal BMI change (odds ratio per SD increase, 1.32 [1.14–1.52]), but not childhood BMI, was associated with middle age CAC score ≥1. This association for pubertal BMI change was maintained after adjustment for midlife BMI at CAC analysis and in a model including major cardiovascular risk factors. Individuals who became overweight during puberty (hazard ratio, 2.11 [1.79–2.49]), but not those overweight at 8 years who normalized their weight during puberty, had substantially increased risk of acute coronary events compared with men who were never overweight. Among subjects with an acute coronary event, individuals with pubertal onset overweight were at increased risk of death due to the event. CONCLUSIONS: Pubertal BMI change is an independent predictor of CAC score and risk of acute coronary events in adult men. Excessive BMI increase during puberty may initiate the coronary atherosclerotic process, thereby increasing the risk and severity of adult acute coronary events.